The therapeutic role of minocycline in Parkinson’s disease - (:unkn) unknown (My University, 2019)
Minocycline, a semisynthetic tetracycline-derived antibiotic, has been shown to exert anti-apoptotic, anti-inflammatory, and antioxidant effects. Furthermore, there is rapidly growing evidence suggesting that minocycline may have some neuroprotective activity in various experimental models such as cerebral ischemia, traumatic brain injury, amyotrophic lateral sclerosis, Parkinson's disease (PD), Huntington's disease, and multiple sclerosis. In this perspective review, we summarize the preclinical and clinical findings suggesting the neuroprotective role of minocycline in PD.
Keywords: neurodegeneration; Parkinson’s disease; minocycline; neuroprotection